Foot‐and‐Mouth Disease in Red Deer – Experimental Infection and Test Methods Performance. Issue 1 (23rd April 2015) - Kittelberger, R.; Nfon, C.; Swekla, K.; Zhang, Z.; Hole, K.; Bittner, H.; Salo, T.; Goolia, M.; Embury‐Hyatt, C.; Bueno, R.; Hannah, M.; Swainsbury, R.; et al.
Summary: The aim of this study was to evaluate a number of foot‐and‐mouth disease (FMD) test methods for use in red deer. Ten animals were intranasally inoculated with the FMD virus (FMDV) O UKG 11/2001, monitored for clinical signs, and samples taken regularly (blood, serum, oral swabs, nasal swabs, probang samples and lesion swabs, if present) over a 4‐week period. Only one animal, deer 1103, developed clinical signs (lesions under the tongue and at the coronary band of the right hind hoof). It tested positive by 3D and IRES real‐time reverse transcription polymerase chain reaction (rRT‐PCR) in various swabs, lesion materials and serum. In a non‐structural protein (NSP) in‐house ELISA (NSP‐ELISA‐IH), one commercial ELISA (NSP‐ELISA‐PR) and a commercial antibody NSP pen side test, only deer 1103 showed positive results from day post‐inoculation (dpi) 14 onwards. Two other NSP‐ELISAs detected anti‐NSP serum antibodies with lower sensitivity. It also showed rising antibody levels in the virus neutralization test (VNT), the in‐house SPO‐ELISA‐IH and the commercial SPO‐ELISA‐PR at dpi 9, and in another two commercial SPO‐ELISAs at dpi 12 (SPO‐ELISA‐IV) and dpi 19 (SPO‐ELISA‐IZ), respectively. Six of the red deer that had been rRT‐PCR and antibody negative were re‐inoculated intramuscularly with the same O‐serotype FMDV at dpi 14. None of these animals became rRT‐PCR or NSP‐ELISA positive, but all six animals became positive in the VNT, the in‐house SPO‐ELISA‐IH and the commercial SPO‐ELISA‐PR. Two other commercial SPO‐ELISAs were less sensitive or failed to detect animals as positive. The rRT‐PCRs and the four most sensitive commercial ELISAs that had been used for the experimentally inoculated deer were further evaluated for diagnostic specificity (DSP) using 950 serum samples and 200 nasal swabs from non‐infected animals. DSPs were 100% for the rRT‐PCRs and between 99.8 and 100% for the ELISAs.